Between Permeability and Isolation: A Comparative Urban Life Study of Inner- City Railway Stations and their Node Precincts in China - Shan He (Athens Journal of Architecture, 2016)
Conventional railway station precincts in Chinese cities have a reputation of being chaotic, dirty, crowded, and even unsafe. This negative image prevents them from integrating into the surrounding urban fabric. Past decades have witnessed a large scale redevelopment of rail infrastructure across China, new relationships between the station and city have been shaped through this period. This paper studies this phenomenon as part of a research that investigates the planning and design practices of the emerging new towns oriented at high-speed rail (HSR) in China. Data collected from 30 surveyed inner-city stations is analyzed to support this study. The author starts with building the scenarios of the existing relationships between inner-city railway stations and their node precincts, through defining and categorizing the concept of SIDA (station and influenced development area). Selected cases, including Xi’an and Beijing South Stations, are then studied to disclose the quality of station-city integration in different SIDA scenarios through the analysis of urban life permeability. The conclusion points out that the integration in studied SIDAs is generally weak. The emerging HSR stations and new towns around them should consider re-inventing permeable lives between both precincts.